Comparative efficacy of three anesthetic protocols on cardiac parameters during ovary-hysterectomy in bitches - Quimbaya Ramírez, John Jaime (2023)
This study aimed to compare the general electrical heart activity, blood pressure, and heart rate when using three anesthetic protocols for ovariohysterectomy in bitches. In total, 33 healthy canines were selected, distributed in 3 groups of 11 animals each, aged between 1 and 3 years, and with a body weight of 8 to 15 kg from shelters in Bucaramanga, Colombia. Three anesthetic protocols in a completely randomized experimental designwere used. Protocol 1: Ketamine (7 mg/kg) + pentobarbital sodium (1 mg/kg); Protocol 2: Ketamine (7 mg/kg) + propofol (3 mg/kg); Protocol 3: Tiletamine + zolazepam (7 mg/kg). The individual outcomes were classified according to the American Society of Anesthesiologists (ASA I). The results showed that parameters evaluated in the surgical phase significantly increased in patients with Protocol 1 (p<0.05). Protocol 2 showed a better performance in the post-surgical phase (p<0.05) compared with others. Patients with Protocol 3 presented fewer alterations in the electrical conduction of cardiac activity than the other protocols, and quicker recovery after the surgery.